Impact of heart motion on radiation dose in the heart and left ventricular myocardium during breast cancer treatment - Xiao, Zhiqing; Wang, Yanqiang; Wang, Miao; Guo, Han; Lin, Xiaotong; Tian, Lei; Liu, Junling; Li, Xiuwu; Xue, Xiaoying (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to investigate changes in the geometric position and dosimetry differences of the heart and the left anterior descending coronary artery (LAD) during radiotherapy with deep inspiration breath hold (DIBH) in patients with left-sided breast cancer after radical mastectomy.MethodsA retrospective analysis was undertaken on 10 patients with left-sided breast cancer who received DIBH radiotherapy. Changes in the motion position of the heart and the LAD and dosimetric differences were compared by analyzing the planning CT and cone beam CT (CBCT) images.ResultsHeart volume was negatively correlated with the heart V5 and Dmean and positively correlated with V30 and Dmax. Changes in the heart volume were positively correlated with the dose changes in both the heart and the LAD. The lateral (X-axis) motion of the heart was positively correlated with the heart V15 and V20 and the LAD Dmax, but negatively correlated with the heart Dmax. Superior–inferior (Y-axis) motion was negatively correlated with the heart V15, V20, V30, and Dmean and changes in the LAD dose. Anterior–posterior (Z-axis) motion was positively correlated with changes in both the heart dose and the LAD V5, V15, and V20 doses. Owing to alterations in the centroids, the heart requires expansions of the planning margins of 1.33, 4.10, and 2.42 mm in the X, Y, and Z directions, respectively, while the LAD requires expansions of 3.13, 1.79, and 5.43 mm in the corresponding directions. The distances of the cardiac boundary boxes during the different sessions showed a positive correlation with the heart V5, V15,V20, V30, and Dmean and a negative correlation with the LAD V5 and Dmax.ConclusionsDuring the implementation of DIBH radiotherapy for the treatment of left-sided breast cancer, dose assessment for the heart and the LAD provided by static CT planning may contain some inaccuracies. Accordingly, it is recommended to reasonably adjust the organ-at-risk external boundaries in the treatment plan to effectively control the doses received by the heart and the LAD, thereby ensuring patient safety.